Information about the Weight of Grasped Objects from Vision and Internal Models Interacts within the Primary Motor Cortex - Loh, Morrison N. (Society for Neuroscience, 2010)
When grasping and lifting different objects, visual cues and previously acquired knowledge enable us to prepare the upcoming grasp by scaling the fingertip forces according to the actual weight of the object. However, when no visual information is available, the weight of the object has to be predicted based on information learned from previous grasps. Here, we investigated how changes in corticospinal excitability (CSE) and grip force scaling depend on the presence of visual cues and the weight of previously lifted objects. CSE was assessed by delivering transcranial magnetic stimulation (TMS) at different times before grasp of the object. In conditions in which visual information was not provided, the size of motor evoked potentials (MEP) was larger when the object lifted was preceded by a heavy relative to a light object. Interestingly, the previous lift also affected MEP amplitude when visual cues about object weight were available but only in the period immediately after object presentation (50 ms); this effect had already declined for TMS delivered 150 ms after presentation. In a second experiment, we demonstrated that these CSE changes are used by the motor system to scale grip force. This suggests that the corticospinal system stores a “sensorimotor memory” of the grasp of different objects and relies on this memory when no visual cues are present. Moreover, visual information about weight interacts with this stored representation and allows the corticospinal system to switch rapidly to a different model of predictive grasp control.